Evaluation of Solubility, Dissolution Rate, and Oral Bioavailability of β-Cyclodextrin and Hydroxypropyl β-Cyclodextrin as Inclusion Complexes of the Tyrosine Kinase Inhibitor, Alectinib - Bashar J. M. Majeed; Mohammed A. Saadallah; Israa H. Al-Ani; Mohamed K. El-Tanani; Khaldun M. Al Azzam; Hassan H. Abdallah; Feras Al-Hajji (MDPI AG, 2024)
This study aims to improve the solubility and dissolution rate of alectinib (ALB), a tyrosine kinase inhibitor commonly used for treating non-small-cell carcinoma (NSCLC). Given ALB's low solubility and bioavailability, complexation with β-cyclodextrin (βCD) and hydroxy propyl β-cyclodextrin (HPβCD) was evaluated. Some of the different preparation methods used with varying ALB-to-CD ratios led to the formation of complexes that were characterized using Fourier-Transform Infrared (FTIR) techniques and Differential Scanning Calorimetry (DSC) to prove complex formation. The encapsulation efficiency was also determined. The simulations were carried out for ALB's interactions with βCD and HPβCD. This study identified the most soluble complex (ALB-HPβCD; 1:2 ratio) and evaluated its dissolution. The bioavailability of the ALB-HPβCD complex was evaluated in Wistar rats relative to free ALB. Pharmacokinetic profiles revealed increased Cmax (240 ± 26.95 ng/mL to 474 ± 50.07 ng/mL) and AUC0-48 (5946.75 ± 265 ng.h/mL to 10520 ± 310 ng.h/mL) with no change in the elimination rate constant. In conclusion, the complexation of ALB-HPβCD manages to increase in vitro solubility, the dissolution rate, and oral bioavailability, providing a favorable approach to improving ALB administration.